Effectiveness of 8-Week Glecaprevir/Pibrentasvir for Treatment-Naïve, Compensated Cirrhotic Patients with Chronic Hepatitis C Infection - Flamm, Steven L. (Adv Ther, 2020)
INTRODUCTION: Glecaprevir/pibrentasvir (G/P) was approved on 26 September 2019 by the US Food and Drug Administration for 8-week duration in treatment-naïve (TN) hepatitis C virus (HCV)-infected patients with compensated cirrhosis (CC). Evidence from the EXPEDITION-8 study demonstrated that 8 weeks of G/P achieved a 98% intent-to-treat (ITT) sustained virologic response rate 12 weeks post treatment (SVR12) in 343 TN/CC patients. The aim of this study is to demonstrate the first US real-world effectiveness of G/P 8-week treatment in genotype 1–6 TN/CC HCV patients. METHODS: Data from 73 TN/CC patients who initiated 8 weeks of G/P treatment between August 2017 and November 2018 were collected electronically from providers and specialty pharmacies of the Trio Health network and analyzed. Cirrhosis was determined by FIB-4 > 5.2 or was physician reported. The primary outcome was Per Protocol (PP) SVR12. RESULTS: The majority (60%) of patients were male, with (mean values): age 59 years, body mass index (BMI) of 30, aspartate aminotransferase (AST) 105, and alanine aminotransferase (ALT) 101 IU/ml. HCV genotypes (GT) were: GT1 81% (59/73), GT2 10% (7/73), GT3 5% (4/73), GT4 3% (2/73), and GT6 1% (1/73). Eight percent (6/73) of patients had concurrent proton pump inhibitor (PPI) use, and 15% (11/72) had a baseline viral load > 6 MM IU/ml. Zero patients discontinued, two patients were reported as lost to follow-up, and there was one virologic failure. PP sustained virologic response at 12 weeks (SVR12) rate was 99% (70/71), and the intent-to-treat (ITT) SVR12 rate was 96% (70/73). CONCLUSIONS: Early real-world experience indicates high effectiveness of the 8-week G/P regimen in a diverse treatment-naïve, compensated cirrhotic US population.